2011
DOI: 10.1007/s00268-011-1166-8
|View full text |Cite
|
Sign up to set email alerts
|

Popular Belief Meets Surgical Reality: Impact of Lunar Phases, Friday the 13th and Zodiac Signs on Emergency Operations and Intraoperative Blood Loss

Abstract: Scientific analysis of our data does not support the belief that moon phases, zodiac signs, or Friday 13th influence surgical blood loss and emergency frequency. Our data indicate that such beliefs are myths far beyond reality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 32 publications
0
24
0
2
Order By: Relevance
“…Famous examples include “Friday the 13th” and a full moon causing an increased number of ED visits. Although several studies have investigated whether such associations exist, no definitive conclusions have been reached [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Famous examples include “Friday the 13th” and a full moon causing an increased number of ED visits. Although several studies have investigated whether such associations exist, no definitive conclusions have been reached [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Jedynie na granicy istotności statystycznej znajduje się zależność pomię-dzy wiekiem mężczyzn a ich znakiem zodiaku oraz częstością urazów. W piśmiennictwie dostępne są zarówno artykuły o wpływie znaku zodiaku na różne choroby, jak i takie, które podważają wpływ gwiazd na człowieka [32,33,34,35,36]. Być może na różnice częstotliwości występowania różnych chorób i urazów wpływu nie ma ułożenie gwiazd, lecz miesiąc urodzenia.…”
Section: Dyskusjaunclassified
“…Scholars indicated that 23% of respondents view themselves as generally superstitious, and that certain specific workrelated superstitions are widespread. A study showed more than 40% of the medical staff is convinced that lunar phases affect human behavior [9]. Another irrational belief implies that leaving hospital on a Saturday is bad luck and 40% of doctors would allow postponement of discharge based on the patients' superstitions [10].…”
Section: Beliefs About Luck Among Healthcare Practitionersmentioning
confidence: 99%